Comparative assessment of matching grants and microcredit interventions in improving livelihood of peasant farmer in Mazabuka District, Zambia - Kabengele, Godfrey (Research of GSB, 2018)
Financing peasant farmers using sustainable and effective approach can reduce poverty level significantly among peasant farmers. Development Institutions and government deploy various financing models to fund peasant farmers as a means of intervention to alleviate poverty. This study assesses and compares two financing model i.e. matching grants and microcredit in order to know which model has greater impact in improving livelihoods of peasant farmers so that it can be advocated for as a model best suited to fund peasant farmers. The respondents for the study are peasant farmers who have accessed funding from Vision Fund Zambia a microcredit institution and Smallholders Agriculture Promotion Program an Institution that provides matching grants. The study is based on assessing livelihood improvement of peasant farmers using Care International framework that is focusing on capabilities, economic activities and assets. A total of one hundred and forty six respondents were selected using simple random procedure. The data was analysed using statistical package for social science (SPSS). Using descriptive statistics and focus group discussions, the finding shows marginal difference in livelihood improvement between microcredit and matching grants on assets and capabilities of the respondents. Matching grants exhibit higher impact on economic activities of the recipients as compared to microcredit. The study recommends that institutions offering matching grants must consider streamlining the process of project approval and disbursement while microcredit institution must tailor their services to client's needs and charge interest taking into consideration the vulnerability context. Overall matching grants are a better model for financing poor and vulnerable peasant farmers.